SERANGAN SERANGGA PERUSAK PADA CONTOH KAYU DI GUDANG PUSAT PENELITIAN DAN PENGEMBANGAN HASIL HUTAN DAN SOSIAL EKONOMI KEHUTANAN BOGOR - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1995)
Since establishment in around 1920, Forest Products and Forestry Socio-economics Research and Development Centre (FPFSRDC) Bogor, Indonesia continuosly collects various wood samples from throughout the country's forest for experimental purposes. Some wood specimens were kept in xylarium as xylotheca, and some others, the rest of experimental samples, were kept in storeroom.An observation was conducted to evaluate deterioration of the wood samples kept in storeroom caused by dry-wood termites, powder-post beetles and pin-hole borers. Of the 464 pieces of wood samples representing 84 wood species, number of samples attacked by dry- wood termites and pin-hole borers was much higher than that by powder-post beetles. Evaluation of the deteriorating grade of the wood samples having been mostly stored for more than 30 years caused by the termites infestation showed that about 37 and 45 %, each represents 38 and 24 wood species, of the wood samples could be respectively categorized into very resistant and resistant, the rest, about 10, 5 and 1 %, each of 15, 6 and 2 species, were classified as moderate, not resistant and very not resistant. Among the highly resistant wood group, 27 species were uninfested at all.Deteriorating grade caused by the pin-hole borers beetles was not recorded, but it seems to be not so important than that caused by the other pests. Even though powder-post beetles only infested a small number of the wood species, they caused heavy damage to their hosts.